The Solace of Sin - Cookson, Catherine (London Bantam Press, 1998)
When her marriage breaks up Constance buy an isolated house on the moors. The people selling her new home demand settlement the very next day. She is surprised by their sense of urgency. Is this really the right way to start life again? Revelations about her husband put her new life under threat
Keywords: Separated people -- Home ownership -- England